Ultranarrow spectral response of InGaAs QDIPs through the optimization of strain-coupled stacks and capping layer composition. (15th March 2017) - Panda, Debiprasad; Balgarkashi, Akshay; Shetty, Saikalash; Ghadi, Hemant; Tongbram, Binita; Chakrabarti, Subhananda
Abstract: The effect of the capping layer and the number of strain-coupled stacks on the optoelectrical properties of In0.5 Ga0.5 As quantum dot infrared photodetectors (QDIPs) are reported in this paper. GaAs-capped and InGaAs-capped bilayer, trilayer, pentalayer, and heptalayer QDIPs were grown for the first time and analyzed. The ground-state photoluminescence emission of all coupled QDIPs redshifted relative to that of the uncoupled QDIPs. All coupled InGaAs-capped QDIPs exhibited monomodal spectral response, whereas among GaAs-capped QDIPs, only the bilayer QDIP exhibited monomodal response. The optimal activation energy (339.87 meV) and full width at half maximum (FWHM; 16 meV) as well as the lowest dark current density (6.5E−8 A/cm 2 ) at 100 K, and −1 V bias were observed for the InGaAs-capped trilayer QDIP among all due to better dot confinement, homogeneity, and also better strain coupling between the vertically stacks QD layers. The peak spectral response at 7.08 µm obtained from this QDIP had an ultranarrow FWHM of 8.67 meV, making it useful for hyperspectral applications in the infrared region.